2018
DOI: 10.1002/jcp.26777
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Effect of PLK1 inhibition on cisplatin‐resistant gastric cancer cells

Abstract: Objective: This study aims to investigate the effect of polo-like kinase 1 (PLK1) inhibition on cisplatin (DDP)-resistant gastric cancer (GC) cells. Methods: The transcriptional level of PLK1 was measured by quantitative reverse-transcription polymerase chain reaction. Expressions of PLK1 and its downstream mediators as well as autophagy-related protein LC3 I/LC3 II were detected by western blot. An 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and 5-ethynyl-2′deoxyuridine immunofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…In this study, we also showed the clinical significance of two hub genes (CHEK2 and PLK1) in the cell cycle pathway and their correlations with FAM189B. Both of these two coexpressed genes of FAM189B have been well reported to play essential roles in the cell cycle regulation and development of GC [30][31][32][33][34]. Although there was only preliminary evidence of a correlation, this finding also suggests that FAM189B may affect the clinical progression of GC by disturbing the cell cycle of GC cells.…”
supporting
confidence: 54%
“…In this study, we also showed the clinical significance of two hub genes (CHEK2 and PLK1) in the cell cycle pathway and their correlations with FAM189B. Both of these two coexpressed genes of FAM189B have been well reported to play essential roles in the cell cycle regulation and development of GC [30][31][32][33][34]. Although there was only preliminary evidence of a correlation, this finding also suggests that FAM189B may affect the clinical progression of GC by disturbing the cell cycle of GC cells.…”
supporting
confidence: 54%
“…33 It has been reported that overexpression of PLK1 can promote the progression of breast cancer, 33 renal cell carcinoma, 34 gastric cancer. 35 With regard to the study of PLK1 in OS, Zhu et al found that the proliferation of OS cells was inhibited with the intervention of PLK1 expression. 36 Mo et al found that PLK1 could promote the proliferation of MYC-amplifying OS cells through autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that WASF3 overexpression induces autophagy by increasing ATG12 level and causes OXA resistance in gastric cancer cells, while interference with WASF3 can reverse OXA resistance in vitro (Nie et al, 2020). Chen et al (2019) have demonstrated that the expression of polo-like kinase 1 (PLK1) is significantly increased in cisplatin (DDP)-resistant SGC-7901/DDP cells, whereas PLK1 knockdown inhibits autophagy, increases apoptosis, and restores the chemosensitivity of DDPresistant cells. Aquaporins (AQPs) are a family of small integral membrane proteins; among them, AQP3 is highly expressed in gastric cancer tissues (Moosavi and Elham, 2020).…”
Section: Regulatory Proteins Inducing Both Autophagy and Chemoresistancementioning
confidence: 99%